2018
DOI: 10.1186/s13287-018-0798-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix stiffness controls osteogenic differentiation of mesenchymal stem cells mediated by integrin α5

Abstract: BackgroundHuman mesenchymal stem cell (hMSC) differentiation into osteoblasts has important clinical significance in treating bone injury, and the stiffness of the extracellular matrix (ECM) has been shown to be an important regulatory factor for hMSC differentiation. The aim of this study was to further delineate how matrix stiffness affects intracellular signaling through integrin α5/β1, FAK, and Wnt signaling, subsequently regulating the osteogenic phenotype of hMSCs.MethodshMSCs were cultured on tunable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 57 publications
(61 reference statements)
4
117
2
Order By: Relevance
“…Evidence suggests a possible direct communication, forming a functional unit, both at mechanical and biochemical levels, with an important role in joint homeostasis. For example, the presence of holes dipping through the calcified cartilage into the bone and marrow spaces and the dense vasculature from subchondral bone found in close proximity with cartilage potentiates the diffusion of nutrients and small molecules between these tissues [80,81]. Chondrocytes are the only cell type residing in adult cartilage, owing low metabolic activity and surviving in a hypoxic environment, in contrast with bone cells residing in the subchondral region.…”
Section: Overview On Soft-to-hard Tissue Interfaces Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests a possible direct communication, forming a functional unit, both at mechanical and biochemical levels, with an important role in joint homeostasis. For example, the presence of holes dipping through the calcified cartilage into the bone and marrow spaces and the dense vasculature from subchondral bone found in close proximity with cartilage potentiates the diffusion of nutrients and small molecules between these tissues [80,81]. Chondrocytes are the only cell type residing in adult cartilage, owing low metabolic activity and surviving in a hypoxic environment, in contrast with bone cells residing in the subchondral region.…”
Section: Overview On Soft-to-hard Tissue Interfaces Physiologymentioning
confidence: 99%
“…compared with substrates such as tissue culture plastic (TCP) (b). Reproduced, with permission, from [81]. Materials stiffness can also influence tendon differentiation.…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Du and colleagues noted that chondrocytes seeded on polyacrylamide of varying stiffness also demonstrated activation of b-catenin and reduction in cartilage markers in a manner that required integrin and FAK phosphorylation (20). Using polyacrylamide coated with fibronectin varying in stiffness from 13-68 kPa, Sun et al also demonstrated an improvement in osteogenic differentiation on stiffer substrates in a manner that required a5b1 integrin signaling resulting in ERK phosphorylation, Akt phosphorylation, and b-catenin activation (23). Both the former studies contrast with our work in that activation of Akt and ERK were uninvolved in our results, potentially secondary to cell type differences or differences in the composition of the materials used.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro results showed that the HA‐PEG hydrogel provided an optimum condition to promote MSC osteogenesis, which is likely due to its mechanical properties, pore size, and porosity. Many studies have proven that the matrix stiffness of the scaffold is a key parameter governing the capacity of in vitro osteogenesis . The study by Chen et al has elicited a correlated relationship of matrix stiffness and the accumulation of bone matrix proteins in 3D hydrogels .…”
Section: Discussionmentioning
confidence: 99%